(untitled) (Aporia, 2021)
This essay provides a novel account of epistemic injustice by changing the standpoint of analysis from the marginalised to the oppressor. Previous investigations into epistemic injustice have shown how members of a marginalised group are harmed as knowers through their own speech. The framework that I will build — incorporating core elements of Fricker and Dotson’s work — focuses on speakers who truncate their own speech in conversation with a member of a marginalised social group, due to a bias against said audience. Testimonial throttling, at its core, is a restriction of access to the pool of knowledge due to bias. While a complete exposition of Fricker and Dotson’s work falls outwith the bounds of this essay, their accounts of ‘testimonial injustice’ and ‘testimonial quieting’, respectively, are instrumental in my account of ‘testimonial throttling’. After describing the foundations of this new account of epistemic injustice, I will propose a set of conditions along with thought experiment that describes a specific instance of testimonial throttling. Having defined testimonial throttling, I show that it covers a gap in the literature and provides insight into a vast array of resultant epistemic and practical harms. Before concluding I discuss a possible recourse for both the speaker and audience to combat testimonial throttling itself.